The Impact of Ecological Checks on Urban Areas Towards Crime Rates in Indonesia - Ahmad Yani (International Journal of Business, Economics, and Social Development, 2022)
This study was conducted to analyze the impact of ecological checks on urban areas towards crime rates. The research was run at the Laboratory of Earth Information at University of Lampung, while the data acquisition was carried out at Subdit IV Tipidter Ditreskrimsus POLDA Lampung on October 2014 - December 2014. This study applied a modeling approach using secondary data from 36 districts/ cities in Indonesia. The model used in this study was multiple linear regression using multiple dummy variables. The response variables used were the level of criminality such as murder, rape, persecution, kidnapping, destruction, theft, fraud, narcotics, and victims of demonstration anarchism. The explanatory variables include the level of regional urbanism and air pollution (air pollution including CO, HC, and CO2) as the main variables which were equipped with accompaniment variables (recreation areas, places of worship and religious leaders). Based on the results of linear regression using Minitab V.16 software at a confidence interval of 5% and 10%, it is showed that the degree of regional urbanism is one of the variables that can cause an increase in criminal rates. Meanwhile, environmental polluting variables (CO, HC, and CO2) have no real effect.